Modified glass fiber filter material for oil-solid two-phase particle air filtration and preparation method thereof

By deposition of modified nanosilicon dioxide on the surface of glass fiber filter material, changing the wettability and roughness of the filter material, the high resistance and short life problems of existing high-efficiency filters when treating oil-solid two-phase particles are solved. It realizes rapid separation and efficient filtration of oiling and solid particles on the filter material.

CN119258656AActive Publication Date: 2025-01-07XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411506458.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

When existing high-efficiency filters treat oil-solid two-phase particles, the low porosity leads to large purification resistance and high energy consumption. The viscosity of oil-solid two-phase particles increases significantly, and even damages the filter material. It cannot effectively improve the purification efficiency of the fine particles of oil-solid phases.

Method used

Modified nanosilicon dioxide is deposited on the surface of glass fiber filter material by impregnation method, and the nanosilicon dioxide is modified using silane coupling agent to change the wetting properties and surface roughness of the filter material, and enhance the oil on the filter fibers The flow capacity of the oil film is inhibited and the filtration resistance is reduced.

Benefits of technology

The rapid separation of oiling and solid particles on the filter material is achieved, the growth rate of pressure drop during the filtration process is reduced, the service life of the filter material is extended, and the filtration efficiency of the oil-solid phase particles is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258656A_ABST
    Figure CN119258656A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oil-solid two-phase particle filtration, and particularly relates to a modified glass fiber filter material for oil-solid two-phase particle air filtration and a preparation method thereof. The modified glass fiber filter material is obtained by depositing a modified nano silicon dioxide solution on the surface of the glass fiber filter material through an impregnation method; wherein the modified nano silicon dioxide is obtained by modifying nano silicon dioxide through a silane coupling agent. Modified nano silicon dioxide is obtained by grafting a functional group with oleophylic performance on the surface of nano silicon dioxide through silane, and then the modified nano silicon dioxide is added on the surface of the filter material to change the surface roughness of the filter material, so that the wettability of the filter material is changed from two aspects, and the separation of deposited oil and solid particles on the filter material can be realized; the oil accumulated on the surface of the filter material is quickly conveyed into the filter material, so that the flowing capacity of the oil on filter fibers is enhanced, the formation of an oil film is inhibited, and the increase rate of pressure drop in the filtering process is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil-solid two-phase particle filtration, and specifically relates to a modified glass fiber filter material for oil-solid two-phase particle air filtration and a preparation method thereof. Background Art

[0002] In the mechanical processing, metal rolling and other industries, due to the evaporation and condensation of metalworking fluids and the splashing of workpiece debris, a large number of fine oil-solid two-phase particles are often generated, such as Figure 1 As shown. The migration and movement of oil mist and solid particles in the workshop is accompanied by complex particle collision and mixing processes, and some oil mist will condense with solid as condensation nucleus. Finally, an oil-solid two-phase particle distribution system with oil phase as the main phase and solid phase particles is formed in the workshop. These particles are characterized by small particle size, high concentration and complex chemical composition. After being inhaled into the human body, they will be deposited deep into the human respiratory tract and cause respiratory tract infection, pneumonia and even cancer and other diseases, seriously endangering human health and environmental quality indoors and outdoors of buildings.

[0003] In existing research, the most important means of efficient purification of oil mist particles is filtering purification equipment, which uses the inertial interception of fiber materials and the diffusion of particles to capture pollutants in the airflow to achieve the purpose of purifying exhaust gas. Filtering equipment can be divided into five types according to the type of fiber material and porosity: primary efficiency, medium efficiency, medium high efficiency, sub-high efficiency and high efficiency filters. For industries such as mechanical processing, high efficiency filters are often used for purification due to the small particle size (generally less than 2.5 microns). However, the low porosity of high efficiency filters leads to large purification resistance and high energy consumption. And when removing oil-solid two-phase particles, the viscosity increases due to the mixing of the two-phase particles, and it is easy to adhere to the windward side, which leads to a significant increase in filtration resistance. In more serious cases, it may even damage the filter material, resulting in energy and economic losses.

[0004] Therefore, in order to effectively improve the efficiency of high-efficiency purifiers for oil-solid two-phase fine particles, the surface modification method is considered to improve the wetting performance of the filter material, improve the oil transport capacity of the filter material, and inhibit the accumulation of oil on the windward surface, thereby achieving the purpose of reducing operating resistance and extending service life. Provide a new research path for the national strategic goals of energy conservation, emission reduction, and green production. Summary of the invention

[0005] The purpose of the present invention is to provide a modified glass fiber filter material for oil-solid two-phase particle air filtration to overcome the above-mentioned technical problems existing in the prior art.

[0006] The object of the present invention is to provide a method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration.

[0007] To this end, the technical solution provided by the present invention is as follows:

[0008] A modified glass fiber filter material for oil-solid two-phase particle air filtration is obtained by depositing a modified nano-silicon dioxide solution on the surface of the glass fiber filter material through an impregnation method;

[0009] The modified nano-silica is obtained by modifying the nano-silica with a silane coupling agent.

[0010] The silane coupling agent is methyltrimethoxysilane, n-octyltriethoxysilane, dodecyltriethoxysilane, isobutyltriethoxysilane or KH560.

[0011] The modified nano silicon dioxide solution is obtained by dissolving the modified nano silicon dioxide in anhydrous ethanol.

[0012] The mass concentration of the modified nano-silicon dioxide solution is 0.01-0.1%.

[0013] A method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration comprises the following steps:

[0014] Step 1) preparing modified nano silicon dioxide powder;

[0015] Step 2) preparing a modified nano-silicon dioxide solution;

[0016] Step 3) preparing modified glass fiber filter material.

[0017] Step 1) The specific method for preparing the modified nano-silicon dioxide powder is as follows: using nano-silicon dioxide with a particle size of 15-30 nm as a solute and anhydrous ethanol and deionized water in a ratio of 3-4:1 as a solvent, preparing a 1-3wt% nano-silicon dioxide suspension, stirring with a constant temperature magnetic stirrer and heating to 65-75° C., adjusting the pH value to 3-4 with anhydrous oxalic acid, dropping 3-4vol% silane coupling agent, and reacting at a constant temperature of 65-75° C. for 5.5-6.5h to obtain a modified nano-silicon dioxide suspension;

[0018] After the modified nano-silica suspension is naturally dried, it is filtered under reduced pressure in batches and dried in a constant temperature drying oven at 100-120° C. for 1.5-2 hours to obtain solid modified nano-silica; the solid modified nano-silica is coarsely ground with a mortar and then added to a nano-crusher to crush it to 15-30 nm to obtain modified nano-silica.

[0019] Step 2) The specific process of preparing the modified nano-silica solution is as follows: dissolving the modified nano-silica in anhydrous ethanol, and stirring at a constant temperature of 65-75° C. for 0.3-0.5 h to obtain the solution.

[0020] Step 3) The specific process of preparing the modified glass fiber filter material is as follows: first, the glass fiber filter material is immersed in a 70-80°C and 50 vol% ethanol solution for 15-20 minutes to wash the binder and dust on the surface of the filter material, and then the washed glass fiber filter material is dried at a constant temperature of 100-120°C for 1.5-2 hours; finally, it is immersed in a modified nano-silica solution for 20-30 minutes, and naturally dried for 24 hours to obtain a modified glass fiber filter material.

[0021] The beneficial effects of the present invention are:

[0022] The modified glass fiber filter material for oil-solid two-phase particle air filtration provided by the present invention is prepared by grafting lipophilic functional groups on the surface of nano-silicon dioxide with silane to obtain modified nano-silicon dioxide, and then adding modified nano-silicon dioxide on the surface of the filter material to change the surface roughness of the filter material, thereby changing the wetting properties of the filter material from two aspects, enhancing the flow ability of oil on the filter fiber, inhibiting the formation of oil film, and achieving the purpose of reducing the running resistance of the filter material.

[0023] The modified glass fiber filter material of the present invention has excellent diffusion performance for oil, can separate the deposited oil and solid particles on the filter material, quickly transport the oil accumulated on the surface of the filter material to the inside of the filter material, inhibit the formation of liquid film, and reduce the growth rate of pressure drop during the filtration process. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of particle generation in the cutting process;

[0025] Figure 2 It is a schematic diagram of the accumulation of oil-solid two-phase particles on the surface of the existing glass fiber filter material and the modified glass fiber filter material of the present invention;

[0026] Figure 3 It is a schematic diagram of the modification principle of nano-silicon dioxide;

[0027] Figure 4 It is a schematic diagram of the modification principle of the glass fiber filter material of the present invention;

[0028] Figure 5 It is the curve of pressure drop of modified glass fiber filter material prepared by modified silica solution with different concentrations over time;

[0029] Figure 6 This is the filtration efficiency change curve of modified glass fiber filter material prepared by modified silica solution with different concentrations for particles with different particle sizes;

[0030] Figure 7 It is the curve of pressure drop variation with time of modified glass fiber filter material prepared by different silanes;

[0031] Figure 8This is the efficiency change curve of modified glass fiber filter materials prepared with different silanes;

[0032] Fig. 9 This is the dust holding capacity variation curve of modified glass fiber filter media prepared with different silanes;

[0033] Fig.10 It is the infrared spectra of nano-silica modified by different silane coupling agents;

[0034] Fig.11 These are the thermogravimetric curves of nano-silica modified with different silane coupling agents. DETAILED DESCRIPTION

[0035] The following is an explanation of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0036] The exemplary embodiments of the present invention are now described with reference to the accompanying drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. These embodiments are provided to disclose the present invention in detail and completely and to fully convey the scope of the present invention to those skilled in the art. The terms in the exemplary embodiments shown in the accompanying drawings are not intended to limit the present invention.

[0037] Unless otherwise specified, the terms (including technical terms) used herein have the commonly understood meanings to those skilled in the art. In addition, it is understood that the terms defined in commonly used dictionaries should be understood to have the same meanings as those in the context of the relevant fields, and should not be understood as idealized or overly formal meanings.

[0038] Example 1

[0039] The present invention provides a modified glass fiber filter material for oil-solid two-phase particle air filtration, which is obtained by depositing a modified nano-silicon dioxide solution on the surface of the glass fiber filter material by an impregnation method;

[0040] The modified nano-silica is obtained by modifying the nano-silica with a silane coupling agent.

[0041] The surface wettability of the filter material depends on the surface energy of the solid and the surface tension of the liquid. The larger the surface energy of the solid, the easier it is to be wetted by the liquid. The surface energy of the glass fiber filter material is determined by the chemical composition and microscopic geometric morphology of the surface. Therefore, the main means to change the wettability of the filter material are: 1. Chemical surface modification, 2. Construction of a rough surface. In order to achieve the change of the wettability of the filter material by the above two methods, the modified glass fiber filter material for oil-solid two-phase particle air filtration provided by the present invention is obtained by grafting lipophilic functional groups on the surface of nano-silica with silane to obtain modified nano-silica, and then adding modified nano-silica to the surface of the filter material to change the surface roughness of the filter material. The obtained modified glass fiber filter material is a super lipophilic material with excellent diffusion properties to oil, such as Figure 2 As shown, the oil deposited on the filter material and the solid particles can be separated, the oil accumulated on the surface of the filter material can be quickly transported to the inside of the filter material, the formation of liquid film can be inhibited, and the growth rate of pressure drop during the filtration process can be reduced.

[0042] Example 2

[0043] Based on Example 1, this example provides a modified glass fiber filter material for oil-solid two-phase particle air filtration, wherein the silane coupling agent is methyltrimethoxysilane, n-octyltriethoxysilane, dodecyltriethoxysilane, isobutyltriethoxysilane or KH560.

[0044] The modification principle of nano silicon dioxide in the present invention:

[0045] like Figure 3 As shown, ① silane reacts with three Si-OC 2 H 5 The group is hydrolyzed into Si-OH bonds, and Si-OH dehydrates and condenses to form siloxane oligomers containing Si-OH groups. ② The hydroxyl groups (Si-OH) in the siloxane oligomers form hydrogen bonds with the hydroxyl groups (-OH) on the surface of nano-silica, and dehydration reactions occur during the heating and curing process, forming covalent bonds with the nano-silica. ③ One silanol group in the silane molecule is covalently bonded to the surface of nano-silica, and the other two silanol groups are condensed or freed with the silanol groups in other silanes.

[0046] Example 3

[0047] On the basis of Example 1, this example provides a modified glass fiber filter material for oil-solid two-phase particle air filtration, wherein the modified nano-silicon dioxide solution is obtained by dissolving the modified nano-silicon dioxide in anhydrous ethanol.

[0048] Schematic diagram of filter material modification principle. Modified nano-silicon dioxide is dissolved in anhydrous ethanol to obtain a modified solution, and the modified nano-silicon dioxide is deposited on the surface of the filter material by an immersion method, which can simultaneously change the roughness of the filter material surface and perform surface chemical modification. Figure 4 shown.

[0049] Example 4

[0050] This embodiment provides a method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration, comprising the following steps:

[0051] Step 1) preparing modified nano silicon dioxide powder;

[0052] Step 2) preparing a modified nano-silicon dioxide solution;

[0053] Step 3) preparing modified glass fiber filter material.

[0054] Step 1) The specific method for preparing the modified nano-silicon dioxide powder is as follows: using nano-silicon dioxide with a particle size of 15-30 nm as a solute and anhydrous ethanol and deionized water in a ratio of 3-4:1 as a solvent, preparing a 1-3wt% nano-silicon dioxide suspension, stirring with a constant temperature magnetic stirrer and heating to 65-75° C., adjusting the pH value to 3-4 with anhydrous oxalic acid, dropping 3-4vol% silane coupling agent, and reacting at a constant temperature of 65-75° C. for 5.5-6.5h to obtain a modified nano-silicon dioxide suspension;

[0055] After the modified nano-silica suspension is naturally dried, it is filtered under reduced pressure in batches and dried in a constant temperature drying oven at 100-120° C. for 1.5-2 hours to obtain solid modified nano-silica; the solid modified nano-silica is coarsely ground with a mortar and then added to a nano-crusher to crush it to 15-30 nm to obtain modified nano-silica.

[0056] Step 2) The specific process of preparing the modified nano-silica solution is as follows: dissolving the modified nano-silica in anhydrous ethanol, and stirring at a constant temperature of 65-75° C. for 0.3-0.5 h to obtain the solution.

[0057] Step 3) The specific process of preparing the modified glass fiber filter material is as follows: first, the glass fiber filter material is immersed in a 70-80°C and 50 vol% ethanol solution for 15-20 minutes to wash the binder and dust on the surface of the filter material, and then the washed glass fiber filter material is dried at a constant temperature of 100-120°C for 1.5-2 hours; finally, it is immersed in a modified nano-silica solution for 20-30 minutes, and naturally dried for 24 hours to obtain a modified glass fiber filter material.

[0058] Example 5

[0059] On the basis of Example 4, this embodiment provides a modified glass fiber filter material for oil-solid two-phase particle air filtration. First, modified nano-silica powder is prepared. Nano-silica with a particle size of 15nm is used as the solute, and anhydrous ethanol and deionized water are used as the solvent in a ratio of 3:1 to prepare a 2wt% nano-silica suspension, which is stirred and heated to 70°C using a constant temperature magnetic stirrer, and the pH value is adjusted to 3-4 with anhydrous oxalic acid, and 3vol% silane coupling agent is slowly added dropwise, and the reaction is carried out at a constant temperature of 70°C for 5.5h to obtain a modified nano-silica suspension. After the modified nano-silica suspension is naturally dried, it is filtered under reduced pressure in batches and dried in a constant temperature drying oven at 120°C for 2h to obtain solid modified nano-silica. After coarsely grinding the solid modified nano-silica with a mortar, add a nano-crusher and crush it to 15nm to obtain modified nano-silica.

[0060] Then, a modified solution was prepared by dissolving 0.03 wt % of modified nano-silica in anhydrous ethanol and stirring at a constant temperature of 70° C. for 0.5 h to obtain a super-lipophilic modified nano-silica solution.

[0061] Finally, a super oleophilic modified glass fiber filter material is prepared. The original filter material used in this embodiment is glass fiber filter paper produced by Chongqing Zaisheng Technology Co., Ltd., and the relevant parameters are shown in Table 1.

[0062] Table 1 Performance parameters of filter materials

[0063]

[0064] The original glass fiber filter material was immersed in a 70°C and 50 vol% ethanol solution for 15 minutes to wash the binder and dust on the surface of the filter material, and the washed glass fiber filter material was dried at a constant temperature of 120°C for 2 hours; thereafter, it was immersed in a modified nano-silica solution for 20 minutes and naturally dried for 24 hours to obtain a super oleophilic glass fiber filter material.

[0065] Example 6

[0066] The concentration of the modified nano-silica solution directly affects the roughness of the filter material surface. The chain length and non-coupling side functional groups of the silane coupling agent affect the roughness and surface modification of the filter material, respectively. Therefore, this embodiment conducts the following experiments on the concentration of the modified nano-silica solution and the influence of different silane coupling agents.

[0067] The experimental device and specific test process can be found in patent CN202222856399.6. The experiment uses oil-solid two-phase particles as the pollution source, with a concentration of 300 mg / m 3 , the oil phase accounts for 80%, and the filtration wind speed is 0.12m / s.

[0068] The present invention is based on a National Natural Science Foundation of China general project, project number 52478104, and project name “Morphological evolution mechanism and efficiency enhancement and resistance reduction method in the process of oil-solid particle self-circulation ventilation purification”.

[0069] 1. Different concentrations of modified nano-silica solution

[0070] According to the preparation process of Example 5, modified nano-silica solutions with mass concentrations of 0.01%, 0.03%, 0.05% and 0.1% were prepared respectively, and then four super-oleophilic modified glass fiber filter materials prepared from modified nano-silica solutions with different concentrations were obtained. Among them, the silane coupling agent was n-octyltriethoxysilane.

[0071] The resistance change curves of four filter materials were measured respectively, and the results are as follows: Figure 5 It can be found that when the concentration of the modified solution is 0.03%, the filter material's resistance growth rate is the slowest and its service life is the longest.

[0072] Study on the efficiency of super oleophilic filter materials prepared by modified nano-silica solutions with different concentrations Figure 6 As shown in the figure (from left to right in the figure are TPM, 0.3-1μm, 1-5μm, >5μm). For particles with a particle size of >1μm, the initial efficiency of the filter material modified with 0.03wt% solution is the highest, among which the initial efficiency of TPM (all total particle size segments of >0.3μm) is 0.9-7.1% higher than that of other filter materials. The final efficiency is not much different. For particles with a particle size of <1μm, when the concentration of the modified solution is >0.05wt%, the filtration efficiency is higher, mainly because the increase in the concentration of the modified solution leads to a decrease in the pores inside the filter material, and small particles are easier to be captured by the filter material.

[0073] 2. Types of silane coupling agents. Five different silane coupling agents were selected to modify nano-silica. Their names and characteristics are shown in Table 2. Nano-silica was modified with the following five silane coupling agents to prepare super-oleophilic glass fiber filter materials. The infrared spectra of nano-silica modified with different silane coupling agents are shown in Fig.10 shown.

[0074] 1100, 800, 465cm -1 The peaks at 2800~3000cm correspond to the Si-O-Si and Si-O bond characteristics of the silica structure, and the change in peak shape reflects the degree of surface modification. -1 The region is the characteristic region of the CH stretching vibration peak. The different peak shapes are due to the differences in CH vibration caused by the introduction of alkyl chains of different lengths and structures by different silanes (especially obvious in samples 2 and 3). -1The region is the stretching vibration peak of the hydroxyl group (-OH), which can be seen to be more prominent in the unmodified silica. This is because the surface hydroxyl groups are consumed by forming silicon-oxygen bonds (Si-O-Si) during the silane modification process.

[0075] Thermogravimetric curve Fig.11 As shown, there are two weight loss steps. At 50-150°C, the weight of the unmodified nano-silica drops sharply, mainly due to the adsorption of water on the surface of the silica. Since the surface of the modified nano-silica is hydrophobic, the weight loss in this temperature range is less than that of the unmodified nano-silica. Fig.11 , from the far right, from top to bottom are the original filter material, silane 1, silane 4, silane 2, silane 5 and silane 3.

[0076] At 200-600℃, the weight loss is more obvious, and the thermogravimetric curves of nano-silica modified with different silanes are obviously different. This is mainly due to the loss of the organic silane layer, and the longer the silane chain length, the greater the weight loss. Therefore, the comprehensive analysis of infrared spectrum and thermogravimetric curve proves that nano-silica is successfully grafted and modified.

[0077] The experiment uses oil-solid two-phase particles as the pollution source, and the concentration is 300 mg / m 3 , oil phase accounts for 80%, filtration wind speed is 0.12m / s, and the resistance and efficiency changes of five filter materials (all obtained by immersing in a modified nano-silica solution with a concentration of 0.03wt% for 20min) are tested. The results are as follows Figure 7 .

[0078] Table 2 Selection of silane coupling agents

[0079]

[0080] The experimental results show that the resistance of the modified glass fiber is reduced to varying degrees compared with the original filter material. The service life of the filter material modified with non-polar functional groups is longer than that of the polar functional groups. At 0.03wt%, the overall short chain has a longer service life than the long chain. The most suitable chain length is n-octyltriethoxysilane, and the service life is increased by 71% compared with the original filter material. Two non-polar methyl functional groups have no advantage over a single methyl functional group.

[0081] Study on the efficiency of super oleophilic modified glass fiber filter materials prepared by different silanes Figure 8As shown. For particles >1μm, the filtration efficiency of the modified filter material is not much different from that of the unmodified filter material (-1.9~6.2%). Among them, the initial and final efficiencies of the filter material modified by silane 2 are increased by 3.4% and 1.6% respectively. For particles <1μm, the initial efficiency of the modified filter material is improved to varying degrees compared with the unmodified filter material. Among them, the initial efficiency of the filter material modified by silane 1 is increased by 15.6% compared with the unmodified filter material, and the final efficiency of the filter material modified by silane 2 is increased by about 1.6% compared with the unmodified filter material.

[0082] like Fig. 9 As shown, the dust holding capacity of the modified filter materials is improved to varying degrees compared with the original filter materials, among which the dust holding capacity of silane 2 and 4 is increased by 30.2% and 32.6% respectively.

[0083] In summary, the modified glass fiber filter material obtained by the present invention can separate the deposited oil and solid particles on the filter material, quickly transport the oil accumulated on the surface of the filter material to the inside of the filter material, enhance the flow ability of the oil on the filter fiber, inhibit the formation of oil film, and reduce the growth rate of pressure drop during the filtration process.

[0084] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.

Claims

1. A modified glass fiber filter material for oil-solid two-phase particle air filtration, characterized in that: It is obtained by depositing the modified nano-silica solution on the surface of the glass fiber filter material by the impregnation method; The modified nano-silica is obtained by modifying the nano-silica with a silane coupling agent.

2. The modified glass fiber filter material for oil-solid two-phase particle air filtration according to claim 1, characterized in that: The silane coupling agent is methyltrimethoxysilane, n-octyltriethoxysilane, dodecyltriethoxysilane, isobutyltriethoxysilane or KH560.

3. The modified glass fiber filter material for oil-solid two-phase particulate air filtration according to claim 1, characterized in that: The modified nano silicon dioxide solution is obtained by dissolving the modified nano silicon dioxide in anhydrous ethanol.

4. The modified glass fiber filter material for oil-solid two-phase particulate air filtration according to claim 1, characterized in that: The mass concentration of the modified nano-silicon dioxide solution is 0.01-0.1%.

5. The method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration according to claim 1, characterized in that: The following steps are involved: Step 1) preparing modified nano silicon dioxide powder; Step 2) preparing a modified nano-silicon dioxide solution; Step 3) preparing modified glass fiber filter material.

6. The method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration according to claim 5, characterized in that: Step 1) The specific method for preparing the modified nano-silicon dioxide powder is as follows: using nano-silicon dioxide with a particle size of 15-30 nm as a solute and anhydrous ethanol and deionized water in a ratio of 3-4:1 as a solvent, preparing a 1-3wt% nano-silicon dioxide suspension, stirring with a constant temperature magnetic stirrer and heating to 65-75° C., adjusting the pH value to 3-4 with anhydrous oxalic acid, dropping 3-4vol% silane coupling agent, and reacting at a constant temperature of 65-75° C. for 5.5-6.5h to obtain a modified nano-silicon dioxide suspension; After the modified nano-silica suspension is naturally dried, it is filtered under reduced pressure in batches and dried in a constant temperature drying oven at 100-120° C. for 1.5-2 hours to obtain solid modified nano-silica; the solid modified nano-silica is coarsely ground with a mortar and then added to a nano-crusher to crush it to 15-30 nm to obtain modified nano-silica.

7. The method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration according to claim 5, characterized in that: Step 2) The specific process of preparing the modified nano-silica solution is as follows: dissolving the modified nano-silica in anhydrous ethanol, and stirring at a constant temperature of 65-75° C. for 0.3-0.5 h to obtain the solution.

8. The method for preparing a modified glass fiber filter material for oil-solid two-phase particle air filtration according to claim 5, characterized in that: Step 3) The specific process of preparing the modified glass fiber filter material is as follows: first, the glass fiber filter material is immersed in a 70-80°C and 50 vol% ethanol solution for 15-20 minutes to wash the binder and dust on the surface of the filter material, and then the washed glass fiber filter material is dried at a constant temperature of 100-120°C for 1.5-2 hours; finally, it is immersed in a modified nano-silica solution for 20-30 minutes, and naturally dried for 24 hours to obtain a modified glass fiber filter material.

Citation Information

Patent Citations

  • A filter media testing system

    CN218865725U

  • Preparation method and application of ultra-hydrophobic and ultra-lipophilic paper-based separating material

    CN102225273A

  • Novel pulse bag filter

    CN106268076A

  • Modified nano-silica, PVDF micro-filtration membrane and application of PVDF micro-filtration membrane

    CN107200848A

  • HDTMS modified silicon dioxide filling PIM-1 composite membrane and preparation method thereof

    CN108554203A